War or peace in the South China Sea? - Kivimäki, Timo (Nordic Institute of Asian Studies NIAS, 2002)
The South China Sea is of great strategic importance and has been the scene of many disputes. The volume covers the historical and legal background of the area, analyses its environmental, economic, military and political dimensions and assesses the potential for containing and resolving disputes